Distribution of Acid Sensing Ion Channels in Axonal Growth Cones and Presynaptic Membrane of Cultured Hippocampal Neurons - Liu, Xiaoyan; Liu, Can; Ye, Jiamin; Zhang, Shuzhuo; Wang, Kai; Su, Ruibin (Frontiers in Cellular Neuroscience, 2020)
Although acid-sensing ion channels (ASICs) are widely expressed in the central nervous system, their distribution and roles in axonal growth cones are unclear. We examined ASICs localization and function in the axonal growth cones of cultured immature hippocampal neurons. Our immunocytochemical data showed that native and overexpressed ASIC1a and ASIC2a are both localized in growth cones of cultured young hippocampal neurons. Calcium imaging experiments and electrophysiological experiments were utilized to validate their function. Calcium imaging tests indicated that the ASICs (mainly ASIC1a) present in growth cones mediate calcium influx despite the addition of voltage-gated Ca 2+ channels antagonists and the depletion of intracellular calcium stores. Electrophysiological tests suggested that a rapid decrease in extracellular pH at the growth cones of voltage-clamped neurons evokes inward currents that were blocked by bath application of an ASIC antagonist amiloride, showing that the ASICs expressed at growth cones are functional. The subsequent immuno-colocalization tests demonstrated ASIC1a and ASIC2a are both colocalized with Neurofilament-H and Bassoon in mature hippocampal neurons. This finding illustrated after reaching maturity, ASIC1a and ASIC2a are both distributed in axons and the presynaptic membrane. Our data reveal the distribution of functional ASICs in growth cones of immature hippocampal neurons and the presence of ASICs in the axons and presynaptic membrane of mature hippocampal neurons, indicating a possible role for ASICs in axonal guidance, synapse formation and neurotransmitter release.